2016
DOI: 10.1111/1462-2920.13334
|View full text |Cite
|
Sign up to set email alerts
|

A HOPS protein, CmVps39, is required for vacuolar morphology, autophagy, growth, conidiogenesis and mycoparasitic functions of Coniothyrium minitans

Abstract: Coniothyrium minitans is an important sclerotial and hyphal parasite of the plant pathogen Sclerotinia sclerotiorum. Previously, a conidiation-deficient mutant, ZS-1N22225, was screened from a T-DNA insertional library of C. minitans. CmVps39, a homologue of Vam6p/Vps39p that plays a critical role in vacuolar morphogenesis in yeast, was disrupted by a T-DNA insertion in this mutant. CmVps39 is composed of 1071 amino acids with an amino-terminal citron homology domain and a central clathrin homology domain, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 48 publications
1
20
0
Order By: Relevance
“…Generally, SNARE associated homotypic fusion processes are mainly regulated by homotypic fusion and protein sorting complex (HOPS) (Hong and Lev, 2014), according to Chen (2016), the HOPS complex principally consists of core subunit (Vps11, Vps16, Vps18, and Vps33) and an accessory subunit (Vps39 and Vps41). Previous research demonstrations have shown that Vps39 and Vps41 inactivity impacted negatively on vacuolar morphology and aggregation (Raymond et al, 1992; Guerra and Bucci, 2016; Medvedev et al, 2016), furthermore, the accessory subunit of the HOPS complex are crucially involved in the promotion of autophagy vegetative growth, conidiation and virulence of many filamentous fungi (Liu et al, 2006; Yang et al, 2016). Previous research findings have shown that MoVps39 a component of the HOPS complex crucially regulate conidiogenesis, appressorium formation, and development of blast infection in M. oryzae.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, SNARE associated homotypic fusion processes are mainly regulated by homotypic fusion and protein sorting complex (HOPS) (Hong and Lev, 2014), according to Chen (2016), the HOPS complex principally consists of core subunit (Vps11, Vps16, Vps18, and Vps33) and an accessory subunit (Vps39 and Vps41). Previous research demonstrations have shown that Vps39 and Vps41 inactivity impacted negatively on vacuolar morphology and aggregation (Raymond et al, 1992; Guerra and Bucci, 2016; Medvedev et al, 2016), furthermore, the accessory subunit of the HOPS complex are crucially involved in the promotion of autophagy vegetative growth, conidiation and virulence of many filamentous fungi (Liu et al, 2006; Yang et al, 2016). Previous research findings have shown that MoVps39 a component of the HOPS complex crucially regulate conidiogenesis, appressorium formation, and development of blast infection in M. oryzae.…”
Section: Introductionmentioning
confidence: 99%
“…After recognizing the presence of S. sclerotiorum, C. minitans penetrates the hyphae of S. sclerotiorum with the help of fungal cell wall-degrading enzymes (fCWDEs) (14,42,43). Decreased expression levels of the exo-␤-1,3-glucanase gene Cmg and the chitinase gene CH1 have been reported in many mutants defective in parasitizing S. sclerotiorum (15,16,18). In this research, the loss of function of CmAim24 was also accompanied by the reduced expression of genes for cell wall-degrading enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Only three orthologs in GH18were shared by C. minitans and Trichoderma spp., but they were not detected during the early stage of interaction between C. minitans and S. sclerotiorum. The chitinase gene (CMZSB_00640) and β-1,3-endoglucanase (CMZS_02526) of C. minitans are usually used as two marker genes for mycoparasitism [63], while their orthologs can also be identified in pathogenic fungi. Furthermore, these two genes and CMZSB_02023 (encoding chitinase) were also up-regulated significantly (log2 ratio > 2.5, FDR ≤ 0.001) at conidiationdata not shown).…”
Section: Discussionmentioning
confidence: 99%